RPP30 is a novel diagnostic and prognostic biomarker for gastric cancer - Kan, Ying; Lu, Xia; Feng, Lijuan; Yang, Xu; Ma, Huan; Gong, Jianhua; Yang, Jigang (Frontiers in Genetics, 2022)
Objective: This study aimed to identify the hub gene in gastric cancer (GC) tumorigenesis. A biomarker prediction model was constructed and analyzed, and protein expression in histopathological samples was verified in a validation cohort. Methods: Differentially expressed genes (DEGs) were identified from GC projects in The Cancer Genome Atlas (TCGA) database. Functional enrichment analysis of DEGs was performed between the high- and low- Ribonuclease P protein subunit p30 (RPP30) expression groups. ROC analysis was performed to assess RPP30 expression to discriminate GC from normal tissues. Functional enrichment pathways and immune infiltration of DEGs were analyzed using GSEA and ssGSEA. Survival analysis and nomogram construction were performed to predict patient survival. Immunohistochemical staining of GC tissues was performed to validate RPP30 expression in GC and paracancerous samples. Results: Gene expression data and clinical information of 380 cases (375 GC samples and 32 para-cancerous tissues) were collected from TCGA database. The AUC for RPP30 expression was found to be 0.785. The G alpha S signaling pathway was the most significantly enriched signaling pathway. Primary therapy outcome (P < 0.001, HR = 0.243, 95% CI = 0.156 - 0.379), age (P = 0.012, HR = 1.748, 95% CI = 1.133 - 2.698), and RPP30 expression (P < 0.001, HR = 2.069, 95% CI = 1.346 - 3.181) were identified as independent prognostic factors. As a quantitative approach, a nomogram constructed based on RPP30 expression, age, and primary therapy outcome performed well in predicting patient survival. Nineteen of the 25 tissue samples from the validation cohort showed positive RPP30 expression in GC tissues, whereas 16 cases showed negative RPP30 staining in normal tissues. The difference between the two was statistically significant. Conclusion: High RPP30 expression was significantly correlated with disease progression and poor survival in GC, promoting tumorigenesis and angiogenesis via tRNA dysregulation. This study provides new and promising insights into the molecular pathogenesis of tRNA in GC.